Merger; Tinjauan Undang-undang Nomor 40 Tahun 2007 Tentang Perusahaan Terbatas dan POJK.03/2018 Tentang Persyaratan Dan Tata Cara Penggabungan, Peleburan, Pengambilalihan, Integrasi Dan Konversi Bank Umum - Siregar, Erpiana (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2020)
This paper is a study that discusses mergers in UUPT 2007 and POJK.03 / 2018 concerning Requirements and Procedures for Merger, Consolidation, Takeover, Integration and Conversion of Commercial Banks. The procedural arrangements of the two arrangements include: design, terms of incorporation. The approval of the board of commissioners is submitted to the GMS for approval, obtaining approval from the relevant agency. Meanwhile, the regulations regarding the protective merger in the 2007 UUPT and POJK.13/2018 are aimed at protecting the interests of related parties, namely the company, minority shareholders, creditors and the public and healthy competition in doing business.